PENGARUH MANAJEMEN MODAL KERJA TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BEI PERIODE 2016-2021 - Prakoso, Bagas Gandhi; Widyarti, Endang Tri (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to examine the effect of working capital management on profitability in stateowned companies listed on the Indonesia Stock Exchange. Profitability is measured using return on assets (ROA). The independent variables used in this study are Inventory turnover in days (ITD), Receivable turnover in days (RTD), accounts payable (PTD), cash conversion cycle (CCC). The sample used in this study are state-owned companies listed on the IDX (Indonesian Stock Exchange) during the 2016-2021 period. The number of samples is 20 companies taken by purposive sample method. The analytical method used is panel data regression with Panel Least Squares with the Eviews: 10 program which has previously passed the classical assumption test. Fixed effect was chosen as the best model